VALENCY RULE AND ALLEGED HOFMEISTER SERIES IN THE COLLOIDAL BEHAVIOR OF PROTEINS : III. THE INFLUENCE OF SALTS ON OSMOTIC PRESSURE, MEMBRANE POTENTIALS, AND SWELLING OF SODIUM GELATINATE. - Kunitz, M. (The Rockefeller University Press, 1924)
A detailed study was made on the influence of salts on those physicochemical properties of sodium gelatinate which are regulated by Donnan's law of membrane equilibria; namely, osmotic pressure, membrane potentials, and swelling. It was found that the influence of salts on these properties in the case of sodium gelatinate obeys the same rules of valency as in the case of the influence of salts on gelatin chloride as discussed in a previous publication. The rules state that when a salt is added to an ionized protein, without causing a change in the hydrogen ion concentration of the protein, the general effect is a depression of the mentioned properties. The degree of depression depends not only on the concentration of the salt but on the electrical properties of the ions constituting the salt. Of the two or more oppositely charged ions of which a salt consists, only the valency of those ions which carry charges opposite to those carried by the protein ions affects the degree of depression which increases with the valency of the ions. It was also found that the phenomenon of swelling of gelatin becomes modified by solubility of the gelatin when salts are added in concentrations higher than N/4. Emphasis is laid on the point that the valency rule holds perfectly also in relation to swelling as long as the phenomenon is pure swelling which is the case when salt solutions of concentrations lower than N/4 are added to gelatin.